Penggunaan Media PowerPoint Interaktif Hiasan dalam Pembelajaran Seni Rupa tentang Mengenal Aneka Ragam Hias dari Berbagai Daerah di Indonesia dalam Tenun NTT untuk Meningkatkan Kreativitas Siswa Kelas V SDN Kelapa Lima - Emerensiana Manehat; Margaretha Djokaho; Maxsel Koro (Lembaga Yasin AlSys, 2025)
The low level of creativity among fifth-grade students at SDN Kelapa Lima in understanding the topic of regional ornamental designs in Indonesia, particularly in the context of tenun from East Nusa Tenggara (NTT) serves as the background for this study, as student learning outcomes had not yet met the Minimum Competency Criteria (KKM) of 70. This study aims to enhance students’ creativity through the use of interactive PowerPoint media on ornamental designs in cultural arts education. The research employed a Classroom Action Research (CAR) method, conducted over two cycles involving the stages of planning, implementation, observation, and reflection. The study involved 25 fifth-grade students, with data collected through observations and tests, and analyzed using descriptive qualitative methods. The findings reveal a significant improvement in both creativity and learning outcomes: learning mastery increased from 64% in the first cycle to 92% in the second; teacher activity rose from 95.83 to 98.61; and student engagement increased from 72.18 to 87.26. The study concludes that the use of interactive PowerPoint media effectively enhances students' creativity, engagement, and understanding of ornamental motifs in tenun NTT. These findings underscore the importance of teachers’ technological proficiency in designing engaging and adaptive instructional media to comprehensively improve student learning outcomes.